Children's Physical Activity, Academic Performance, and Cognitive Functioning: A Systematic Review and Meta-Analysis - Sember, Vedrana; Jurak, Gregor; Kovač, Marjeta; Morrison, Shawnda A.; Starc, Gregor (Frontiers in Public Health, 2020)
Researching the relationship between physical activity and academic performance is becoming an important research topic due to increasing evidence about the positive effect of physical activity on cognitive functioning. The present systematic review and meta-analysis (PROSPERO registration number: CDR132118) is a unique contribution to the recently published reviews since it only includes interventions longer than 6 weeks and acknowledges the influence of the qualifications of practitioners who deliver interventions. After identifying 14,245 records in five databases and selecting 247 full-text articles assessed for eligibility, 44 interventions passed all eligibility criteria. This meta-analysis uses validity generalization in a random effects model, which shows that academic performance itself is not solely caused by increased physical activity. The weighted mean population effect of all included interventions was rw=0.181. Most of the studies had serious limitations since they did not report physical activity intensity, which is an essential component to achieving positive exercise effects on cognition. In addition, the qualifications of the staff who administer the interventions were largely ignored in existing literature. It was found that 13 out of 20 physical activity interventions with significant positive effects on academic performance were performed by practitioners who held higher qualifications in the field of physical education and exercise science, who could mediate higher physical activity intensities of the given interventions. The population effect in studies where interventions were administered by practitioners with lower qualifications in the field (rw=0.14) was lower compared to interventions performed by staff with higher qualifications (rw=0.22). There was also a significant difference in academic performance with regard to staff qualification level (χ=4.464; p=0.035). In addition to activity duration, future physical activity intervention studies including those investigating academic performance should focus on the importance of physical activity intensity and include measures of physical fitness as objective indicators to enable more reliable analyses to establish physical activity influence on academic performance.